Management of Congenital Macroglossia Due to Lymphatic Malformation in a Child with Review of Literature - Sushma Achugatla; Surendra Singh; Sonia Thakur; Rajeev Redkar (Journal of Indian Association of Pediatric Surgeons)
Lymphangiomas are uncommon congenital hamartomas of the lymphatic system with a marked predilection for the head-and-neck region accounting for 75% of all cases. Lymphangiomas rarely affect the oral cavity. Affected sites in the oral cavity may include the tongue, palate, gingiva, lips, and alveolar ridge of the mandible. The anterior two-thirds on the dorsal surface of the tongue is the most common site for intraoral lymphangiomas leading to macroglossia, similar to the presentation in our case. Congenital macroglossia is a rare clinical condition characterized by an enlarged tongue. This enlargement can lead to a variety of oral and facial problems, with structural deformities such as diastema, disproportionate mandibular growth, and functional disorders such as difficulty in eating and swallowing, speech impairment, or even difficulty in breathing if it is severe. Macroglossia may be attributed to multiple underlying causes. These include conditions such as idiopathic muscular hypertrophy (notably in Beckwith–Wiedemann syndrome), vascular malformations (such as angiomas and lymphangiomas), tumors, and endocrine disorders. Among these causes, lymphangiomatous macroglossia is particularly rare and is characterized by diffuse involvement. This type of macroglossia typically progresses chronically, reaching a developmental plateau at puberty without any spontaneous regression. We report a case of congenital macroglossia in an 8-year-old male due to lymphatic malformation and managed successfully.